O tempo de trabalho dos psicólogos: um estudo a partir da luta pela redução da jornada de trabalho - Sampaio, Camilla Regya de Figueiredo Dias (2016)
The struggle for working time reduction configures as one of the biggest laborist claims of all laborer movement history. The pursuit of working time also enables the reflection about life and self-control towards labor time, which emerge as an important starting point for worker subject relation with their own time comprehension. After a latency period, arise in Brazil movements coming up from several professional categories aiming for workload reduction for thirty hour per week, maximum. One of those professional categories is Psychologists, objects of the present study. Among all exposed issues, reducing working time for conciliate more than one job is one of them. The need for multiple employment bonds is related to precarious conditions and low wages. In light of this, eight interviews with Psychologists about their labor time and fight for thirty-hour work week were arranged. The discourse sociological analysis has been chosen as a method to interpret the collected data, finding a comprehension and representation model for concrete text of their social and history context. Such interpretation highlighted a huge fragmentation in the professional category, which enables the individuation of those Psychologists whom did not take part in working time reduction discussion in a collective way. Besides that, precariousness naturalization and productivity discourse assimilation could be noticed, emerging, foremost, from neoliberal ideology widespread. According such ideology, professional pursuit, through themselves, punctual modifications to ease the precarious conditions. In Psychologists example, they get a second job and fight for labor time reduction. Such struggle seems to contribute to intensify exploration relationships more than to propitiate worker’s emancipation.